New 1, 1'‐Ferrocene Bis(sulfonyl) Reagents. Issue 20 (9th December 2016) - Chanawanno, Kullapa; Holstrom, Cole; Nemykin, Victor N.; Herrick, Richard S.; Ziegler, Christopher J.
Abstract: Several new 1, 1'‐bis(sulfonyl)ferrocenes designed for the synthesis of sulfonamide linked biological conjugates have been prepared. 1, 1'‐Bis(sulfonylbromide)ferrocene can be produced from the corresponding sulfonylchloride via a bis(sulfonylhydrazide) intermediate. Bis(sulfonyl‐ N ‐hydroxybenzotriazole)ferrocene can also be synthesized from the sulfonyl chloride, and reaction of glycine methyl ester with the sulfonyl chloride affords a [3]ferrocenophane complex. All new compounds have been structurally characterized by X‐ray crystallography. Abstract : New 1, 1'‐bis(sulfonyl)ferrocenes designed for the synthesis of sulfonamide linked biological conjugates have been prepared. 1, 1'‐Bis(sulfonylbromide)ferrocene can be produced from the corresponding sulfonylchloride via a bis(sulfonylhydrazide) intermediate. Bis(sulfonyl‐ N ‐OBt)ferrocene can be synthesized from the sulfonyl chloride, and reaction of glycine methyl ester with the sulfonyl chloride affords a [3]ferrocenophane complex.